Gold-catalyzed alkynylative meyer-schuster rearrangement - Banerjee, Somsuvra; Ambegave, Shivhar B.; Mule, Ravindra D.; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2020)
By applying the ``interplay'' mode, which consolidates two key reactivity modes of gold catalysis, namely pi-activation mode and cross-coupling mode, the first alkynylative Meyer-Schuster rearrangement is designed and successfully implemented. The current protocol gives straightforward access to enynones, a highly valuable building block, from easily available propargyl alcohol feedstocks. Control experiments suggest an Au(III) catalyst triggers the Meyer-Schuster rearrangement, whereas monitoring the reaction with ESI-HRMS provided strong evidence in favor of a key alkynylgold(III) intermediate which supports the proposed ``interplay'' scenario.